Knowledge Discovery, Knowledge Engineering and Knowledge Management - Fred, A (Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 5th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management, IC3K 2013, held in Vilamoura, Portugal, in September 2013. The 27 full papers presented together with two invited papers were carefully reviewed and selected from 239 submissions. The papers are organized in topical sections on knowledge discovery and information retrieval; knowledge engineering and ontology development; knowledge management and information sharing.